Investigating risk factors for developing autism, cerebral palsy and down syndrome in a Trinidadian population - Sagireddy, Sowmya; Nayak, Shivananda B.; Brewster, Natasha; Nanan, Varsha; Harry, Rajiv; Ali, Mikhail; Fraser, Alexander; Greaves, Rachelle; Singh, Visham; Barclay, Sally (International Journal of Research in Medical Sciences, 2019)
Background: Autism, Cerebral Palsy and Down Syndrome are three lifelong, non-curable common developmental disorders that affect approximately 1 in 59, 1 in 323, and 1 in 700 children respectively. This research is to study the effects of prenatal, perinatal, and postnatal factors on the development of Autism, Cerebral Palsy (CP) and Down Syndrome (DS) in a Trinidadian population. Methods: This was a descriptive case-control study comprised 75 subjects, with 25 cases from each of the three disorders investigated, i.e. autism, CP and DS. Results: The highest risk of autism was associated with mothers having high stress levels (p=0.002), high blood pressure (0.042), and low iron levels (p=0.012) during the pregnancy, as well as having a family history of autism (p=0.002) and residing in an air polluted area (p=0.034). The highest risk of cerebral palsy was associated with a child being born preterm (case 24%, control 0; p=0.009), experiencing postnatal complications (case 80%, control 4%, p=0.000), having a birth weight less than 2500 g (p=0.002), having an abnormal appearance at birth (p=0.045), specifically the prevalence of blue baby (case 20%, control 0) and abnormal appearance (case 12%, control 4%), a case father having a low educational level (p=0.002), a case of mother having gestational diabetes during the pregnancy (p=0.037) and having older mothers (p=0.033) and fathers (p=0.033) than the controls. The highest risk of down syndrome was associated with mothers having high stress (p=0.017) and blood pressure (p=0.021) during pregnancy. Conclusions: The findings of our research confirm that autism, CP and DS are multi-factorial developmental disorders. A combination of environmental conditions, genetics, prenatal and postnatal factors are associated with an increased risk of developing autism, cerebral and down syndrome.